Environmental Dependence of all the Five Band Luminosities of Active Galactic Nucleus (Agn) Host Galaxies - Yong Xin; Xin-Fa Deng (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Using the apparent-magnitude limited active galactic nucleus (AGN) host galaxy sample of the Sloan Digital Sky Survey Data Release 12 (SDSS DR12), we investigate the environmental dependence of u-, g-, r-, i- and z -band luminosities of AGN host galaxies. Используя выборку родительских галактик AGN с ограниченной видимой величиной из Sloan Digital Sky Survey Data Release 12 (SDSS DR12), мы исследовали зависимость светимостей в u, g, r, i и z полосах от окружающей среды родительских галактик AGN.
Keywords: Astrophysics